Oxygen isotopes in waters of the Central Arctic Ocean - V Y Vetshteyn; GA Malyuk; V P Rusanov (PANGAEA, 2011)
18? distribution in the Central Arctic Basin was studied. Surface water down to 200 m was found to contain minimum of 18O (-4.5 to -0.6 per mil relative to SMOW). The highest 18O concentration with d18? varying within very narrow limits (from -0.4 to +0.3 per mil) was observed in intermediate Atlantic waters between 200-250 m and 700 m. 18O concentration in the bottom water layer also varied insignificantly (from 0.0 to -0.7 per mil) tending to decrease downward. A comparison of 18O concentration with water salinity and temperature showed that the relation between d18O and salinity may be used to determine a source diluting oceanic water. Proportion of fresh waters was only approximately estimated. Correlation between oxygen isotopic in water and temperature was observed only within a narrow depth range in the surface layer.
Supplement to: Vetshteyn, VY et al. (1974): Oxygen-18 distribution in the central Arctic Basin. Translated from Okeanologiya, 1974, 14(4), 642-648, Oceanology, 14, 514-519